Dynamics of endoreduplication in developing barley seeds - Nowicka, Anna; Kovacik, Martin; Tokarz, Barbara; Vrána, Jan; Zhang, Yueqi; Weigt, Dorota; Doležel, Jaroslav; Pecinka, Ales (Journal of experimental botany, 2021)
Seeds are complex biological systems comprising three genetically distinct tissues: embryo, endosperm, and maternal tissues (including seed coats and pericarp) nested inside one another. Cereal grains represent a special type of seeds, with the largest part formed by the endosperm, a specialized triploid tissue ensuring embryo protection and nourishment. We investigated dynamic changes in DNA content in three of the major seed tissues from the time of pollination up to the dry seed. We show that the cell cycle is under strict developmental control in different seed compartments. After an initial wave of active cell division, cells switch to endocycle and most endoreduplication events are observed in the endosperm and seed maternal tissues. Using different barley cultivars, we show that there is natural variation in the kinetics of this process. During the terminal stages of seed development, specific and selective loss of endoreduplicated nuclei occurs in the endosperm. This is accompanied by reduced stability of the nuclear genome, progressive loss of cell viability, and finally programmed cell death. In summary, our study shows that endopolyploidization and cell death are linked phenomena that frame barley grain development.
Keywords: super cycle value; Hordeum vulgare; cell death; Hordeum; endoreduplication; Endosperm; Cell cycle; endosperm; semena rostlinná; buněčný cyklus; Cell Cycle; Endoreduplication; ječmen (rod); seed development; endoreduplikace; embryo; Seeds